Intensive chemotherapy and consolidation with high dose therapy and autologous stem cell transplant in patients with mantle cell lymphoma. Issue 2 (February 2015) - Nastoupil, Loretta J.; Shenoy, Pareen J.; Ambinder, Alex; Koff, Jean L.; Nooka, Ajay K.; Waller, Edmund K.; Langston, Amelia; Seward, Miray; Kaufman, Jonathan L.; Bernal-Mizrachi, Leon; King, Nassoma; Lechowicz, Mary Jo; et al.
Abstract Mantle cell lymphoma (MCL) remains incurable with conventional chemotherapy without consensus on the optimal initial treatment. We examined our single center experience with frontline therapy for patients with MCL in consecutive cases diagnosed 1995-2011. Among 81 patients, median age was 59 (28% were ≥ 65 years of age), 95% had stage III/IV disease and 54% had a low risk MCL International Prognostic Index score. Thirty-five percent (n = 28) received R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone) and 65% received R-HCVAD (rituximab, hyperfractionated cyclophosphamide, vincristine, doxorubicin, dexamethasone alternating with high-dose methotrexate/cytarabine; n = 53). Forty-one patients were consolidated with autologous stem cell transplant (ASCT). There were no significant differences in 2-year survival for R-CHOP versus R-HCVAD (p = 0.10) or for ASCT versus observation (p = 0.06). After controlling for clinical factors, R-HCVAD followed by ASCT was associated with superior progression-free survival (hazard ratio 0.26, 95% confidence interval 0.09–0.75).